Cardioprotective effect of substance P in a porcine model of acute myocardial infarction. (15th November 2018) - Sim, Doo Sun; Kim, Weon; Lee, Kyung Hye; Song, Ho Chun; Kim, Ja Hye; Park, Dae Sung; Lim, Kyung Seob; Woo, Jong Shin; Hong, Young Joon; Ahn, Youngkeun; Hong, Hyun Sook; Son, Youngsook; et al.
Abstract: Background: Substance P (SP) may attenuate ischemia-reperfusion injury by reducing inflammation. We assessed cardioprotective effect of SP in a porcine model of acute myocardial infarction (AMI). Methods: AMI was induced by occlusion of the left anterior descending artery on 28 swine, randomized to SP 5 nmol/kg (group 1, n = 14) and normal saline (group 2, n = 14) given intravenously 5 min before reperfusion. Blood samples were collected at baseline, 3 days and 4 weeks. Echocardiography and myocardial perfusion single photon emission computed tomography (SPECT) were performed at 1 week and 4 weeks. Histomorphometric infarct size assessment was done at 4 weeks. Results: Left ventricular (LV) ejection fraction (EF) (LVEF) after AMI induction was higher in group 1 than group 2 (37.9 ± 4.6% vs. 29.4 ± 3.2%, p = 0.001) but not different at 4 weeks. No significant difference was observed in perfusion defect extent and total perfusion defect on SPECT at 1 week and 4 weeks. Pathologic infarct size (% LV) was significantly smaller in group 1 than group 2 (2.4 ± 2.3% vs. 5.7 ± 2.5%, p = 0.020). The ratio of neutrophil to lymphocyte on day 3 and serum creatinine concentration at 4 weeks after AMI were lower in group 1. Conclusions: In a porcine model of AMI, SP improved LVEF early post-MI and reduced infarct size. SP may be beneficial in reducing inflammation and ischemia-reperfusion injury after AMI. Highlights: Substance P may attenuate ischemia-reperfusion injury after AMI. Substance P improved LV function early post-MI and reduced infarct size after AMI. Substance P reduced inflammation after AMI.